THE USE OF MODIFIED ENGLISH SONG TO IMPROVE VOCABULARY - Nuzulur Rohmah; Rohmani Nur Indah (Eltin Journal : Journal of English Language Teaching in Indonesia, 2021)
Songs have an important role in the development of children learning a second language. The proof is the frequency of songs used in English teaching classes around the world. The author begins why song can be considered a valuable pedagogical tool. In particular, it will discuss how songs can help learners improve vocabulary mastery. This study aimed to see a significant difference in vocabulary acquisition between students who were taught using Modified English Song and those who were not. This study involved 40 students of Al-Falah Pacul-Bojonegoro Superior Junior High School as the object of research. The result revealed a substantial difference in vocabulary mastery between students in the experimental class who were taught using Modified English Song as a medium and those who were not. The experimental class' average post-test score was 86.80, while the control class' average score was 82.80. Because the t-observation value is higher than t-table (2.6539>1.685), the alternative hypothesis is accepted, and the null hypothesis is rejected, according to the t-test result. Finally, the utilization of Modified English Song can help students increase their vocabulary mastery.